Expressed sequence tags for bovine muscle satellite cells, myotube formed-cells and adipocyte-like cells. - Eun Ju Lee (Public Library of Science (PLoS), 2013)
Background Muscle satellite cells (MSCs) represent a devoted stem cell population that is responsible for postnatal muscle growth and skeletal muscle regeneration. An important characteristic of MSCs is that they encompass multi potential mesenchymal stem cell activity and are able to differentiate into myocytes and adipocytes. To achieve a global view of the genes differentially expressed in MSCs, myotube formed-cells (MFCs) and adipocyte-like cells (ALCs), we performed large-scale EST sequencing of normalized cDNA libraries developed from bovine MSCs. Results A total of 24,192 clones were assembled into 3,333 clusters, 5,517 singletons and 3,842contigs. Functional annotation of these unigenes revealed that a large portion of the differentially expressed genes are involved in cellular and signaling processes. Database for Annotation, Visualization and Integrated Discovery (DAVID) functional analysis of three subsets of highly expressed gene lists (MSC233, MFC258, and ALC248) highlighted some common and unique biological processes among MSC, MFC and ALC. Additionally, genes that may be specific to MSC, MFC and ALC are reported here, and the role of dimethylarginine dimethylaminohydrolase2 (DDAH2) during myogenesis and hemoglobin subunit alpha2 (HBA2) during transdifferentiation in C2C12 were assayed as a case study. DDAH2 was up-regulated during myognesis and knockdown of DDAH2 by siRNA significantly decreased myogenin (MYOG) expression corresponding with the slight change in cell morphology. In contrast, HBA2 was up-regulated during ALC formation and resulted in decreased intracellular lipid accumulation and CD36 mRNA expression upon knockdown assay. Conclusion In this study, a large number of EST sequences were generated from the MSC, MFC and ALC. Overall, the collection of ESTs generated in this study provides a starting point for the identification of novel genes involved in MFC and ALC formation, which in turn offers a fundamental resource to enable better understanding of the mechanism of muscle differentiation and transdifferentiation.